Analysis of Senior High School Students' Problem Solving Ability on Three Variables Linear Equation System - Pratama, M. Faizal; Fitriani, Nelly; Nurfauziah, Puji (IKIP Siliwangi, 2024)
This study aims to analyze students' mathematical problem solving ability on the material of the Three Variable Linear Equation System (SPLTV) in terms of students' initial mathematical abilities. This research was conducted using a qualitative descriptive method, the subjects of this research were 20 students of class X SMA Negeri 1 Cililin who had studied SPLTV material. The data collection technique in this study was to give a written test in the form of a description with a total of four problem solving indicator questions. Before starting the research, the questions were validated first. Based on the results of the study, the percentage of mathematical problem solving ability on the material of the system of linear equations of three variables is 52.23% which is classified in the moderate category. The indicator of understanding the problem is 71.67%, the indicator of planning problem solving is 51.25%, the indicator of solving the problem according to the plan is 48%, and the indicator of making a mathematical model of the problem, solving and re-examining the answer is 38%. The mathematical initial ability of upper group students obtained an average score of 83.3% classified in the high category, the middle group obtained an average score of 74.58% in the high category, and the lower group obtained an average score of 77% which fell into the high category. So it can be concluded that the initial mathematical ability of students is in the high category for mathematical problem solving ability.